Government Size, the Composition of Public Spending and Economic Growth in Netherland - Nartea, Gilbert; Hernandez, Jacqueline (Journal of Accounting, Business and Finance Research, 2020)
The performance of the fiscal policy is influenced significantly by the relationships and associations among the governmental size, the composition public and private spending and the economic growth of a country. The primary goal of this research study is to evaluate the impact of these factors and to evaluate the significance of these factors in the economic growth of the Netherlands. The economy of Netherlands is characterized as the 17th largest in the world and it presents stable and sustainable growth. In this altercation the researcher aimed to evaluate the significance of the governmental spending and size. For this purpose, the researcher used the data from 2004-2014 from the 12 provinces of Netherlands. The data was subjected to a unit root analysis so that the stationarity properties of the panel data can be evaluated. The unit root test results showed that the variables were stationary at I(0). In order to abstain from the endogeneity issues that can be present in such types of datasets the researcher used level and per capita variables as a robustness evaluation. The empirical framework was based upon the Cobb-Douglas production function and used the modern CES substitution elasticities to compute as the inputs of private capital and government spending in the production function. The nonlinear least-squares regression estimation method was used to evaluate the impact of the variables upon one another. The results indicate that the public investments and current governmental disbursements are conjoined in order to account for the inflexibility of the communal budget. Moreover, the governmental spending was found to be greater than 85 percent indicating that the provincial sectors are focused upon the stimulation of the economy.